2023
DOI: 10.31557/apjcp.2023.24.6.1993
|View full text |Cite
|
Sign up to set email alerts
|

A Systems Biology Approach to Identify Novel Biomarkers in Progression from Crohn’s Disease to Colorectal Cancer

Abstract: Objective: This study aimed to find the key genes and miRNAs as potential biomarkers related to the progression of colorectal cancer (CRC) from Crohn’s disease (CD). Background: CD is widely accepted as one of the main risk factors leading to CRC. So, Identifying the novel molecular pathways involved in the development of CRC from CD can provide potential solutions for therapeutic interventions. Methods: By implementing a systematic approach,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Shokrollah et al. have shed light on potential novel biomarkers for CD patients in the tumorigenesis of colorectal cancer 35 . This is relevant as it suggests a deeper link between IBD and other systemic diseases, offering new insights into their shared mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shokrollah et al. have shed light on potential novel biomarkers for CD patients in the tumorigenesis of colorectal cancer 35 . This is relevant as it suggests a deeper link between IBD and other systemic diseases, offering new insights into their shared mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…patients in the tumorigenesis of colorectal cancer. 35 disease, psoriasis is also related with many diseases and numerous studies have already established the relationship between psoriasis and other diseases like depression, nonalcoholic steatohepatitis, and IBD. [36][37][38][39][40][41] Our previous work focused on the comorbidity mechanism between psoriasis and nonalcoholic steatohepatitis, and identified several key genes as potential therapeutic targets using bioinformatics methods.…”
Section: Shokrollah Et Al Have Shed Light On Potential Novel Biomarke...mentioning
confidence: 99%
“…[ 79 , 80 ] Studies have identified key genes and molecular pathways in the progression of CD and colorectal cancer. [ 81 ] During inflammation, recruitment of the above-mentioned immune cells leads to the secretion of highly genotoxic oxygen/nitrogen active substance, [ 82 ] pro-inflammatory cytokines such as interleukin (IL-6), IL-8, IL-1β, TNF-α, and growth factors. [ 83 ] The production of these mediators is mediated by several major signaling pathways, including nuclear factor kB, signal transduction and transcriptional activator 3, PI3K/AKT, and cyclocoxidase-2/prostaglandin E2.…”
Section: Intestinal Micro-ecological Alterations Induce Intestinal Di...mentioning
confidence: 99%
“…To achieve this, many studies has been conducted to investigate the role of long non-coding RNAs (lncRNAs) in modulating various biological processes of CRC cells through intricate lncRNA–mRNA regulatory networks. These studies aim to shed light on the initiation, progression, and metastasis of CRC, ultimately leading to improved strategies for early detection, effective treatment, and better patient outcomes [ 4 7 ].…”
Section: Introductionmentioning
confidence: 99%